A longitudinal study of confabulation. (February 2017) - Dalla Barba, Gianfranco; Brazzarola, Marta; Marangoni, Sara; Barbera, Claudia; Zannoni, Ilaria
Abstract: Confabulation, the production of statements and actions that are unintentionally incongruous to the subject's history, background, present and future situation, is a rather infrequent disorder, observed in several conditions affecting the nervous system. Little is known about the quantitative and qualitative evolution of confabulation in time. In this study we evaluated longitudinally the evolution of this disorder in a group of severe confabulators, using the Confabulation Battery (CB), a sensitive tool to detect confabulations in various memory domains. It was found that confabulations were stable over time and not temporally limited. It was also found that "Habits Confabulations" (HCs), i.e., habits and repeated personal events mistaken as specific, unique past and future personal episodes, or well-known public events when semantic knowledge is concerned, was the more frequently observed type of confabulation. Confabulations were also more prominent in the domain of Temporal Consciousness (TC), i.e., a specific form of consciousness that allows individuals to remember their personal past, to be oriented in their present world and to predict their personal future, than in Knowing Consciousness (KC), i.e., a specific form of consciousness allowing individuals to be aware of past, present and future impersonal knowledge and information. Confabulations showed also persistence, i.e., confabulations at the same questions over time, and consistency, i.e., same type of confabulation at the same question over time. These findings are discussed within the framework of the Memory, Consciousness and Temporality Theory.